Development Model Learning to Train Pencak Silat Tapak Suci - Subardi, Muhammad Bakhtiar; Sulaiman, Sulaiman; Setyawati, Heny; Syaifullah, Rony (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The inappropriateness of early childhood athlete training has a negative impact for athletes, especially the learning to train stage of 9-12 year old boys and 8-11 years old girls on psychological aspects, physiological aspects and physical aspects. The purpose of this research is to improve basic motion skills and produce a product of the learning model book to train pencak silat tapak suci. The method used by Ploomp's Research and Development. (1) Training needs of athletes and coaches (2) Development stage (3) Assessment stage (4) Systematic and reflection. The results of the study were hand games, types of foot games and combination games in support of improving motion skills with standard pre-test deviation of 14.5 and post-test 7.2. Analysis of T-test test data showed a sig value = 0.000 because the sig value < 0.05 then H0 was rejected and it was concluded that there was a significant difference in training using the learning to train model, and there was an increase in the mean pre-test score to the post test with a value of 41.8 to 80.36 so that the learning model to train the Sacred Site significantly improved the ability of basic motion and was very good and worthy of use by the kader of tapak suci trainers.